MEMBANDINGKAN PROSES PENGOLAHAN AIR SUNGAI UNTUK MENGHASILKAN KUALITAS AIR BERSIH - Iswadi, Didik; Febrianti, Febrianti; Lutvi, Lutvi (Ensiklopedia of Journal, 2024)
Nowadays there's a lot of river water that's actually polluted. Clean water is difficult to obtain and very much needed by society. The use of clean water is widespread enough for society, agriculture and industry. The purpose of this study is to find out the difference between river water analysis results using coagulation, to know the impact of coagulant comparisons, to find the best sample results. Research procedure by making a solution by mixing 1, 2, 3, 4, 5, 6 grams of aluminum sulfate into each container containing 200 ml of river water sample and mixing the solution. Then mix each mixture of the solution into each container containing 1 liter of river air sample. So beware of different times.  Then shake for six hours. Then analyze a sample of the river water solution that has been mixed with aluminum sulfate in relation to pH, rigidity, TDS and DHL. In this study obtained samples S1 to S5 can lower the pH, rigidity, TDS and DHL values in the tested river water samples. Of the test results, S3 was the most effective because of its pH:8.2, stiffness:4.08 NTU, TDS:204.46 mg/L, DHL:120.05 μS/cm with values close to standard quality. Tobacco made of natural ingredients that can lower pH, TDS and DHL levels.Keywords: River water, Coagulation, Aluminum sulfate, TDS.